Sistem Informasi Reporting Sales And Marketing Berbasis Web (Studi Kasus Amaroossa Hotels Indonesia) - Fridayanti, Ni Putu Yulia; Sudiatmika, I Putu Gede Abdi; Putra, Ida Ayu Gde Suwiprabayanti (Universitas Tabanan, 2023)
Marketing Sales Department is one of the most important departments in Amaroossa Hotel Indonesia. The purpose of this research is to build a data processing information system of reports from sales and marketing where the source of data from sales and marketing reports be it daily, weekly, monthly reports, and so forth. The application development method uses the waterfall method which starts from the requirements analysis, system and software design, system implementation, and system testing. Whereas for system design using Data Flow Diagrams (DFD) and system development methods are built using Visual Studio Code for coding purposes using the PHP programming language by applying laravel framework. The results of this study produce a website-based system of management of report data from sales and marketing, where the system has several features such as file upload, file view, and file download. Testing system testing uses blackbox testing where testing that has been done on the system produces the conclusion that the system is running well.